Internal resistance and temperature change during over-discharge of lead-acid battery - Balázs Broda; György Inzelt (Journal of Electrochemical Science and Engineering, 2018)
In recent decades, more and more electronic systems (start-stop, drive-by-wire, brake-by-wire) have been developed in the automotive industry therefore reliable power sources are necessary. It is essential to understand thoroughly the detailed behavior of the battery to increase its efficiency, stability and monitorability which is the most popular field nowadays. Over-discharge plays an important role in aging because it increases the probability of initiation of grid corrosion, sulfation and loss of active mass. In this work, the effects of over-discharge of lead-acid battery have been investigated via internal resistance increase and temperature change separately for both the negative and the positive electrode. Most of the measurements were carried out in a prepared test cell (which contained a negative and a positive plate, an Ag│Ag2SO4 reference electrode, a shunt for measuring current accurately) connected to a dummy battery and an electronic load.